Sexual double standard: A gender-based prejudice referring to sexual freedom and sexual shyness - Gómez-Berrocal, Carmen; Moyano, Nieves; Álvarez-Muelas, Ana; Sierra, Juan Carlos (Frontiers in Psychology, 2022)
This study contributes to understanding the factors that favor the inconsistency with which SDS manifests. We used a descriptive methodology to analyze the association between: 1) SDS adherence and individual (i.e., sex, gender role, social dominance orientation, and age) and contextual factors (i.e., perceived normativity of sexual gender norms and areas of sexual behavior: sexual freedom and sexual shyness) and 2) four SDS adherence typologies (SDS man-favorable, SDS woman-favorable, egalitarian and ambivalent) with the same individual and contextual factors. Using data from the general Spanish population (N = 1,206), the results showed, first, that the conceptualization of SDS as a heterosexual gender prejudice allows us to understand the ingroup favoritism bias involved in SDS adherence. That is, attitude toward sexual freedom, unlike SDS adherence in the sexual freedom domain, does not differentiate between men and women, and SDS adherence is more strongly related to men's gender role than to women's gender role. Second, the domain of sexual behaviors related to sexual shyness (vs. domain related to sexual freedom) discriminates better between the different SDS adherence typologies. Third, the results obtained about the explanatory power of individual and contextual factors on the SDS adherence typologies underline the importance of adopting different levels of analysis to understand SDS.